Management of non-Hodgkin lymphomas associated withchronic viral infections - Tőrők-Vistai, Tünde (Medicine and Pharmacy Reports, 2011)
The number of viruses known to have pathogenetic and therapeutic impli-cations in non-Hodgkin lymphomas (NHL) has increased significantly during the last years. Some of these viruses have direct oncogenic effect, for exemple Epstein-Barr virus, Human T-cell lymphotropic virus-1 or human herpesvirus-8, while others cause lymphoma due to chronic antigenic stimulation (like hepatitis C virus) or due to immunosuppression associated with the virus, which is the case of human immunodeficiency virus. Beside their role in pathogenesis, lymphoma-associated viral infections have major therapeutic implications. Treatment of these lymphomas is difficult because of the risk of reactivation after immunosuppressive treatment which could cause severe organ-damage (like severe hepatitis in case of hepatitis virus B or C reactivation), resulting sometimes in the reduction of the scheduled doses or even treatment discontinuation. These patients should be monitored carefully and antiviral therapy should be associated to chemotherapy. In other cases, especially in indolent NHL (for example splenic marginal zone lymphoma associated with hepatitis C virus), antiviral therapy alone could lead to regression of lymphoma. Recognizing this category of NHL is important because correct management of them could improve survival of the patients.